The Relationship Between Attitude Toward Science and Academic Achievement in Science: A Three-Level Meta-Analysis - Mao, Peipei; Cai, Zhihui; He, Jinbo; Chen, Xinjie; Fan, Xitao (Frontiers in Psychology, 2021)
Science education is attracting increasing attention and many researchers focus on the issue about the attitude-achievement relationship in science, but there is still no consistent conclusion. By using a three-level meta-analytic approach, the aim of the current study was to investigate the relationship between attitude towards science and academic achievement in learning science among primary and secondary school students, and to explore if some study characteristics could have contributed to the inconsistent findings with regard to this relationship as observed in the research literature. Twenty-four studies with 85 effect sizes involving a total of 51,793 participants were identified. The meta-analytic results revealed that there was an overall positive and moderate relationship between attitude towards science and learning achievement in science (r = 0.244, p < 0.001). The results further found that this association was moderated by type of attitude and larger effect sizes were shown in self-efficacy than in interest, societal relevance of attitude towards science, and mixed attitude. Possible explanations for these findings and its implications for future research directions were also discussed in this review.